SOLUTION-BASED DEPOSITION OF TRANSPARENT EU-DOPED TITANIUM OXIDE THIN FILMS FOR POTENTIAL SECURITY LABELING AND UV SCREENING - Molkenova, Anara; Khamkhash, Laura; Zhussupbekova, Ainur; Zhussupbekov, Kuanysh; Sarsenov, Sagyntay; Taniguchi, Izumi; Shvets, Igor V.; Atabaev, Timur Sh. (MDPI, 2020)
Transparent titanium oxide thin films attract enormous attention from the scientific community because of their prominent properties, such as low-cost, chemical stability, and optical transparency in the visible region. In this study, we developed an easy and scalable solution-based process for the deposition of transparent TiOx thin films on glass substrates. We showed that the proposed method is also suitable for the fabrication of metal-doped TiOx thin films. As proof-of-the-concept, europium Eu(III) ions were introduced into TiOx film. A photoluminescence (PL) study revealed that Eu-doped TiOx thin films showed strong red luminescence associated with 5D0→7Fj relaxation transitions in Eu (III). We found that prepared TiOx thin films significantly reduce the transmittance of destructive UV radiation; a feature that can be useful for the protection of photovoltaic devices. In addition, transparent and luminescent TiOx thin films can be utilized for potential security labeling.
Keywords: transparent thin film; titanium oxide; europium (III) doping; security labeling; UV screening; Type of access: Open Access